Tips for Effective Implementation of Virtual Reality Exposure Therapy in Phobias—A Systematic Review - Krzystanek, Marek; Surma, Stanisław; Stokrocka, Małgorzata; Romańczyk, Monika; Przybyło, Jacek; Krzystanek, Natalia; Borkowski, Mariusz (Frontiers in Psychiatry, 2021)
Background: The high incidence of phobias and the limited accessibility of psychotherapy are the reasons for the search for alternative treatments that will increase the availability of effective treatment. The use of virtual reality (VR) technology is an option with the potential to overcome the barriers in obtaining an effective treatment. VR exposure therapy (VRET) is based on a very similar rationale for in vivo exposure therapy. The study aimed to answer the question of how to perform exposure therapy in a virtual reality environment so that it is effective. Methods: A systematic review of the literature, using PRISMA guidelines was performed. After analysis of 362 records, 11 research papers on agoraphobia, 28 papers on social phobia and 10 about specific phobias were selected for this review. Results: VRET in agoraphobia and social phobia is effective when performed from 8-12 sessions, on average once a week for at least 15 minutes. In turn, the treatment of specific phobias is effective even in the form of one longer session, lasting 45-180 minutes. Head mounted displays are an effective technology for VRET. Increasing the frequency of sessions and adding drug therapy may shorten the overall treatment duration. The effectiveness of VRET in phobias is greater without psychiatric comorbidity and on the condition of generating and maintaining in the patient a sense of immersion in the VR environment. Long-term studies show a sustained effect of VRET in the treatment of phobias. Conclusion: A large number of studies on in VR exposure therapy in phobias allows for the formulation of some recommendations on how to perform VRET, enabling the effective treatment. The review also indicates the directions of further VRET research in the treatment of phobias.